2009
DOI: 10.1007/s00534-009-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of pathological staging systems in predicting recurrent hepatocellular carcinoma after liver transplantation

Abstract: The current AJCC tumor-node-metastasis staging and the LCSGJ system are superior in predicting HCC recurrence after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There are some relatively recent studies suggesting that the TNM system has the highest predictive value after liver transplantation. 37,38 Unfortunately, the TNM system has other limitations, including a broad tumor range in stage 2, at which transplantation may be considered.…”
Section: What Are the Best Hcc Staging Systems For Making Decisions Amentioning
confidence: 99%
See 1 more Smart Citation
“…There are some relatively recent studies suggesting that the TNM system has the highest predictive value after liver transplantation. 37,38 Unfortunately, the TNM system has other limitations, including a broad tumor range in stage 2, at which transplantation may be considered.…”
Section: What Are the Best Hcc Staging Systems For Making Decisions Amentioning
confidence: 99%
“…Additional staging features that are prognostically important and can be diagnosed by an examination of the explanted liver include microscopic vascular invasion, satellite nodules, and lymph node metastases. 37,[59][60][61][62] Important prognostic information can also be obtained from features that are related to the tumor grade rather than the stage, such as differentiation (including nuclear size/atypia and mitotic activity). A 4-point grading scheme proposed by Edmondson and Steiner in 1954 is still widely cited in studies of prognostic factors for recurrence.…”
Section: What Staging System Is Best For Determining the Prognosis Afmentioning
confidence: 99%
“…The prognosis is evaluated according to these criteria. However, it has been observed that a number of Predicting tumor recurrence using metabolic indices of 18 F-FDG PET/CT prior to orthotopic liver transplantationfor hepatocellular carcinoma patients with similar clinical features display a different prognosis profile according to the Milan criteria (4,5). Therefore, the biological characteristic of tumors must be considered when evaluating patient prognosis.…”
Section: Introductionmentioning
confidence: 99%